2021
DOI: 10.3390/bs11110154
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine/Hydroxychloroquine Use and Suicide Risk: Hypotheses for Confluent Etiopathogenetic Mechanisms?

Abstract: Chloroquine (CQ) and hydroxychloroquine (HCQ) are classical anti-malarial and anti-inflammatory treatments, which were used as first-line therapy at the beginning of the 2019 coronavirus disease (COVID-19) pandemic. Besides the emerging data on their lack of efficacy against COVID-19 infection, such treatments have been associated with some severe health concerns, including those of neuropsychiatric nature, such as a possible increase in suicide risk. Here we report a case of a patient with no history of psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…A total of 22 psychiatric adverse effects were mentioned, which the most common were auditory hallucinations, increased psychomotor activity, irritable mood, suicide ideation, and visual hallucinations (Supplemental Table S1). One study 79 reported a suicide attempt. Psychiatric adverse effects for 3 case reports reemerged, respectively, in 2 weeks, 72 3 weeks, 65 3 months, 68 and 5 years 8 after HCQ was reintroduced.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 22 psychiatric adverse effects were mentioned, which the most common were auditory hallucinations, increased psychomotor activity, irritable mood, suicide ideation, and visual hallucinations (Supplemental Table S1). One study 79 reported a suicide attempt. Psychiatric adverse effects for 3 case reports reemerged, respectively, in 2 weeks, 72 3 weeks, 65 3 months, 68 and 5 years 8 after HCQ was reintroduced.…”
Section: Resultsmentioning
confidence: 99%
“…It remains an open question whether long-term antimicrobial treatment may have contributed to the progression of neurological symptoms in reported patient. Two of the drugs he used are suspected to have neurological or neuropsychiatric side effects, namely minocycline (64)(65) and hydroxychloroquine (66)(67)(68). Either long-term or repeated antibiotic therapy of PTLDS also carries a number of other risks, including development of significant, even life-threatening disorders such as necrotising enterocolitis or systemic candidiasis (69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy might be explained by the absence of a direct and acute impact of SARS-CoV2 infection on vulnerable neurobiological circuits underlying SI/SB development. However, while a direct and acute impact may be absent, it is essential to consider that indirect effects, such as chronic residual low-grade inflammation, the use of certain medications like chloroquine, and the gradual development of psychiatric symptoms, including depression and anxiety [15,[38][39][40][41][42][43], may still play a significant role in predicting a possible rise in SI/SB risk during the post-acute phase of SARS-CoV-2 infection.…”
Section: Suicide Risk and Covid-19mentioning
confidence: 99%